Architecture Students' Perception of AI in Academic Project Resolution - Ulfaizah Sahril Nurfadhilah; Wahyu Saputra (Universitas Negeri Gorontalo, 2024)
This study aims to examine architecture students' perceptions of the role of artificial intelligence (AI) in supporting the completion of academic tasks, ranging from text-based assignments to design processes. Data were collected through an online survey using Google Forms with semi-open and closed-ended questions, involving 289 undergraduate architecture students from six universities in Sulawesi Island. Data analysis was conducted using descriptive statistics and Chi-Square tests with SPSS version 26. The findings indicate that AI is well-received by architecture students, despite their limited understanding of the technology, highlighting the need for enhanced AI training and educational courses in academic institutions. Currently, AI is primarily used for non-design tasks; however, there is significant potential for AI applications in design processes. These tools can enhance students' creativity by facilitating brainstorming and providing inspiration. A balanced implementation of AI is crucial to mitigate potential negative impacts on originality and credibility. This study underscores the importance of developing AI technologies that are more relevant to the needs of architectural education and targeted training to maximize the benefits of AI in both academic and professional contexts.